2011
DOI: 10.1593/neo.101088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of H-Ras-Specific Motif for the Activation of Invasive Signaling Program in Human Breast Epithelial Cells

Abstract: Increased expression and/or activation of H-Ras are often associated with tumor aggressiveness in breast cancer. Previously, we showed that H-Ras, but not N-Ras, induces MCF10A human breast epithelial cell invasion and migration, whereas both H-Ras and N-Ras induce cell proliferation and phenotypic transformation. In an attempt to determine the sequence requirement directing the divergent phenotype induced by H-Ras and N-Ras with a focus on the induction of human breast cell invasion, we investigated the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Ras genes are involved in a wide variety of human tumor types and there is a known positive correlation between HRAS activation and breast cancer (33). In addition, previous studies (34,35) have shown that HRAS can induce invasion and migration of the breast cancer cell line, MCF10A. From the present study, HRAS may serve a significant role in the pathogenesis of TNBC and, given its functional significance in various types of cancer, it may also be a potential therapeutic target in the treatment of TNBC.…”
Section: Discussionsupporting
confidence: 70%
“…Ras genes are involved in a wide variety of human tumor types and there is a known positive correlation between HRAS activation and breast cancer (33). In addition, previous studies (34,35) have shown that HRAS can induce invasion and migration of the breast cancer cell line, MCF10A. From the present study, HRAS may serve a significant role in the pathogenesis of TNBC and, given its functional significance in various types of cancer, it may also be a potential therapeutic target in the treatment of TNBC.…”
Section: Discussionsupporting
confidence: 70%
“…Although the cultured CTCs obtained from patient AMC-15-06 did not have any of the COSMIC database identified mutations also identified in the primary tumor tissue, a mutation of HRAS was detected in CTCs of this patient that has previously been reported to be associated with breast cancer recurrence and metastasis (27,28). …”
Section: Discussionmentioning
confidence: 78%
“…71 A high level of MMP-9 expression was detected at sites of inflammation, thus promoting migration of inflammatory cells across the basement membrane. 72 Interestingly, we have previously shown that MMP-2, rather than MMP-9, is responsible for the invasive phenotype induced by H-Ras and G a12/13 in MCF10A human breast epithelial cells, [73][74][75][76] suggesting differential regulation of MMP-2 and MMP-9, depending on the type of stimuli.…”
Section: Discussionmentioning
confidence: 99%